Growing location and root maturity impact on the phenolic compounds, antioxidant activity and nutritional profile of different sweet potato genotypes - Pazos, Juliana; Zema, Paula; Corbino, Graciela Beatriz; Gabilondo, Julieta; Borioni, Rodrigo Hector Ezequ; Malec, Laura (Elsevier, 2022)
This study aimed to analyze the phenolic compounds, antioxidant activity, and the main nutritional components of different colored-fleshed sweet potato genotypes grown in Argentina. Three cultivars of standard size were compared to undersized ones, currently discarded. Furthermore, four genotypes grown in different agroecological locations in Tucuman, Argentina, were evaluated. Chlorogenic and 3,5-dicaffeoylquinic acids were identified as the prevailing phenolic compounds in all samples. Undersized roots had significantly higher phenolics, antioxidant activity and carotenoids than standard. Therefore, they can confer healthy attributes to processed foods and, additionally, reduce waste. Genotypes from Tucuman grown under water stress conditions presented the lowest phenolics, anthocyanins and antioxidant activity, but the highest carotenoid contents. Orange-fleshed cultivars showed the highest protein percentages (6.0–11.7 %) and carotenoid contents ranging between 310 and 1012 µg β-carotene/g dw, with more than 90 % β-carotene. These findings could help to promote the cultivation of local genotypes with high added value.